2015
DOI: 10.1177/0192513x15590686
|View full text |Cite
|
Sign up to set email alerts
|

Gender Equality in the Family and Childbearing

Abstract: Gender equality and equity in the division of household labor may be associated with couples' transitions to first, second, and third births. Our comprehensive analysis includes the division of housework and childcare as well as the perception of whether this division is fair and satisfactory. We use a unique dataset combining the Norwegian Generations and Gender Survey (2007) with information on childbirths within three years after the interview from the population register. We found that an unequal division … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 38 publications
0
47
0
1
Order By: Relevance
“…Analyses for the Nordic countries provide partial support for the existence of a positive relationship between gender equality and fertility, including at the individual level. Studies have shown that the equal division of housework between spouses encourages childbearing in Norway (Dommermuth, Hohmann-Marriott, and Lappegård 2015), and that larger contributions to childcare by fathers increase second birth risks in Denmark (Brodmann, Esping-Andersen, and Güell 2007). Fathers' uptake of parental leave has been found to be positively associated with continued childbearing in Sweden and Norway (Oláh 2003;Duvander and Andersson 2006;Duvander, Lappegård, and Andersson 2010).…”
Section: Gender Equality and Fertility In Nordic Countriesmentioning
confidence: 99%
“…Analyses for the Nordic countries provide partial support for the existence of a positive relationship between gender equality and fertility, including at the individual level. Studies have shown that the equal division of housework between spouses encourages childbearing in Norway (Dommermuth, Hohmann-Marriott, and Lappegård 2015), and that larger contributions to childcare by fathers increase second birth risks in Denmark (Brodmann, Esping-Andersen, and Güell 2007). Fathers' uptake of parental leave has been found to be positively associated with continued childbearing in Sweden and Norway (Oláh 2003;Duvander and Andersson 2006;Duvander, Lappegård, and Andersson 2010).…”
Section: Gender Equality and Fertility In Nordic Countriesmentioning
confidence: 99%
“…In addition, a rather traditional division of domestic labor, in which the woman was doing most of the work, was associated with a higher transition to family formation. Even though more than half of the childless couples reported that they were sharing routine housework rather equally, this arrangement did not foster family formation, as has been shown for Norway (Dommermuth, Hohmann-Marriott, and Lappegård 2017) and for Finland (Miettinen, Lainala, and Rotkirch 2015). The results for Germany suggest that processes of traditionalization that are conducive to family formation start prior to the birth of a first child.…”
Section: Resultsmentioning
confidence: 83%
“…Moreover, recent research suggests that in Germany the adherence to stereotypical gender roles is still quite common, since fathers report the highest level of life satisfaction when working full-time or even longer (Schröder 2018). Although the majority of previous studies on this topic suggested that an equal division of housework and child care -and, to an even greater extent, the perception that this division is equitable -is advantageous for continued childbearing, especially in countries with a strong emphasis on egalitarian gender roles, such as the Scandinavian societies (e.g., Brodmann, Esping-Andersen, and Güell 2007;Dommermuth, Hohmann-Marriott, and Lappegård 2017;Goldscheider, Bernhardt, and Brandén 2013;Miettinen, Lainala, and Rotkirch 2015), we were unable to replicate these findings for young cohorts of couples in Germany. Instead, women's main responsibility for domestic work had a positive impact on the timing of a second birth with the same partner, while the division of child care and the perception of fairness had no noticeable effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there are studies indicating that the types of policies have different influences on fertility (Ang 2013;Cygan-Rehn 2016), and some have shown that mothers' use of leave has an influence on continued childbearing (for example Lalive and Zweimuller 2009;Matysiak and Szalma 2014). Studies on fathers' childcare and housework engagement, both obviously related to leave use, also indicate that engagement is generally positively associated with continued fertility but to a different degree by context and socioeconomic group (Cooke 2004(Cooke , 2009Torr and Short 2004;Goldscheider, Bernhardt, and Brandén 2013;Nagase and Brinton 2017;Dommermuth, Hohmann-Marriott, and Lappegård 2017;Kato, Kumamaru, and Fukuda 2018). This finding raises further questions as to whether and to what extent the association between fathers' leave-taking and subsequent childbearing is shaped by the amount of sharing, the different norms of gender-equal parenting that the amount of sharing represents (policy-conforming vs. egalitarian), the configuration of the policies, the timing of the introduction and context of the policies, and the use of the policies with the first or a subsequent child.…”
Section: Introductionmentioning
confidence: 99%